Spirituality and Addiction - Flanagan, Bernadette; Molina, Noelia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue includes articles which discuss the longstanding recognition of diverse connections between spirituality and addiction, as well as emerging discussions regarding the spiritual dimensions of addiction treatments. The overall focus is on the overlaps between the journey into addiction and the spiritual journey, informed by the insight of Carl Jung that addictive craving and the seeking of ultimate meaning may be intimately connected. The multiplicity of forms which addiction can assume in contemporary society are the scope of the issue. The overall purpose of the Special Issue is to extend the range of manifestations of addiction which are part of a discussion relating to the soul of recovery. Through this extended agenda of forms of addiction, the Special Issue supplements existing literature on the subject of spirituality and addiction.